Multi-Epigenetic Landscapes of Schizophrenia: Epigenetic Landscapes of Schizophrenia - Saeed, Sarmad Basit; Afzal, Samia; Shahid, Muhammad; Sarmad, Samreen (Pakistan Journal of Health Sciences, 2025)
Schizophrenia is a debilitating neurodevelopmental disorder affecting approximately 1% of the global population. Traditional genetic models have provided limited insight into its complex etiology. This review synthesizes recent advances in epigenetic research related to schizophrenia, focusing on dynamic and reversible genome modifications. The study analyzed multi-omics and epigenomic profiling studies published between 2020 and 2025 that explore DNA methylation, histone modifications, non-coding RNAs and gene–environment interactions in schizophrenia. Epigenetic mechanisms, including DNA methylation, chromatin remodeling and non-coding RNAs, mediate environmental influences during critical neurodevelopmental periods, contributing to long-term gene expression changes associated with schizophrenia. These findings integrate genetic liability with environmental exposures and highlight potential biomarkers and therapeutic targets. Understanding schizophrenia through the lens of epigenetics may inform novel diagnostic and treatment approaches, advancing precision psychiatry.